The Influence of Work Discipline, Quality of work life (QWL) and Work Environment on Work Motivation and Its Impact on the Performance of MSME Employees in Pasuruan Regency - Moc Aminudin Hadi; Andri Wibowo; Agung Edy Wibowo; Mahben Jalil; Titok Waskito Adi (Enrichment : Journal of Management, 2022)
This study aims to analyze the effect of work discipline, QWL and work environment on work motivation and its impact on the performance of MSME employees in Pasuruan Regency. The data of this study were obtained from questionnaires, observations and related literature studies according to the research objectives. The analysis technique uses path analysis with SPSS program. The number of samples is 95 respondents using the incidental sampling technique. The results showed that the variables of work discipline, QWL and work environment had a significant effect either partially or simultaneously on work motivation. Performance of Pasuruan Regency MSME employees. The results showed that work discipline, QWL and work environment had a significant effect either partially or simultaneously on the performance of MSME employees in Pasuruan Regency with work motivation as an intervening variable